Creating personalised energy plans: from groups to individuals using Fuzzy C Means Clustering - Dent, Ian; Wagner, Christian; Aickelin, Uwe; Rodden, Tom
Changes in the UK electricity market mean that domestic users will be required to modify their usage behaviour in accordance with energy eciency targets. Clustering allows usage data, collected at the household level, to be clustered into groups and assigned a stereotypical prole which may be used to provide individually tailored energy plans. Fuzzy C Means extends previous work based around crisp K means clustering by allowing a household to be a member of multi- ple customer prole groups to dierent degrees, thus provid- ing the opportunity to make personalised oers to the house- hold dependent on their degree of membership of each group. In addition, feedback can be provided on how household's changing behaviour is moving them towards more "green" or cost eective stereotypical usage.